How do commodity futures respond to macroeconomic news? - Dieter E. Hess; He Huang; Alexandra Niessen-Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2008)
This paper investigates the impact of seventeen US macroeconomic announcements on two broad and representative commodity futures indices. Based on a large sample from 1989 to 2005, we show that the daily price response of the CRB and GSCI commodity futures indices to macroeconomic news is state-dependent. During recessions, news about higher (lower) inflation and real activity lead to positive (negative) adjustments of commodity futures prices. In contrast, we find no significant reactions during economic expansions. We attribute this asymmetric response to the state-dependent interpretation of macroeconomic news. Our findings are robust to several alternative business cycle definitions.
Keywords: E44; G14; 330; Commodities; Macroeconomic Announcements; Business Cycle; Rohstoff-Futures; Makroökonomischer Einfluss; Konjunkturprognose; USA